2012
DOI: 10.1182/blood-2011-06-361535
|View full text |Cite
|
Sign up to set email alerts
|

Safety of anticoagulants in children with arterial ischemic stroke

Abstract: Pediatric arterial ischemic stroke (AIS) is increasingly diagnosed and carries significant risks of recurrence, morbidity, and mortality. Anticoagulant therapy (ACT) is commonly prescribed in childhood AIS. Hemorrhagic complication rates in pediatric stroke are unknown, and adult safety data are of limited applicability. We analyzed a prospectively enrolled cohort of children (aged 1 month-18 years) with acute AIS selected using standardized criteria for protocol-based ACT over 14-year period. We assessed ACT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…7 Recurrence was observed in 10 children, of whom 6 were not receiving any antithrombotics at the time of recurrence. 23 In our experience, when an otherwise healthy child with AIS presents with an intracranial unilateral focal arterial stenosis and is promptly treated by aspirin until the arteriopathy stabilizes or regresses, the risk of recurrence is low. …”
mentioning
confidence: 99%
“…7 Recurrence was observed in 10 children, of whom 6 were not receiving any antithrombotics at the time of recurrence. 23 In our experience, when an otherwise healthy child with AIS presents with an intracranial unilateral focal arterial stenosis and is promptly treated by aspirin until the arteriopathy stabilizes or regresses, the risk of recurrence is low. …”
mentioning
confidence: 99%
“…We thought that giving subcutaneous LMWH would be preventive, and it would not hinder in case of acute surgical intervention necessity would come up for the patient, and we did not start mannitol treatment at the beginning of the stroke. Clinical investigations reported that use of LMWH for acute ischemic stroke in children is safe [13][14][15][16][17], but no comparative study showing the efficacy or superiority of these drugs including acetylsalicylic acid,warfarin,heparine and ultra-fractionated heparine [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…The use of medication is controversial; anticoagulation is usually considered safe in children and is not contraindicated in oncologic patients unless additional bleeding risk factors (eg, recent surgery, active bleeding, low platelet count <50 × 10 9 /L, uncorrected disseminated intravascular coagulation, or uncontrolled severe malignant hypertension) are present. 14,15 However, primary management is symptomatic, including identification and elimination of any precipitating or aggravating factors. Additional treatment may include analgesics, antiepileptic drugs for seizures, and treatment of arterial hypertension.…”
Section: Discussionmentioning
confidence: 99%